Managing technology and middle- and low-skilled employees : advances for economic regeneration - Hughes, Claretha; Robert, Lionel; Frady, Kristin; Arroyos, Adam (Emerald Publishing Limited, 2019)
As technological change and digital disruption becomes normalized in the fourth industrial revolution, workplace leaders are seeking new solutions to evolving problems. Managing Technology and Middle- and Low-Skilled Employees is an illuminating study of workplace leadership for improving the employee experience and adjusting the organizational culture to reduce tensions between technology and people at work. Reliance on artificial intelligence has created apprehension and anxiety among some employees and the general public as they try to understand whether or not employees will be replaced by new technologies. This book examines technological developments, such as artificial intelligence and big data, and reveals the practical implications of how people and new technologies can co-exist, harmoniously, within the workplace through virtual teams. Managing Technology and Middle- and Low-Skilled Employees offers routes to new solutions for scholars and professionals in the fields of business, human resource development, human resource management, information systems, and workforce development.
Includes index.
Keywords: Technological innovations.; Employees -- Effect of technological innovations on.; Business & Economics -- Human Resources & Personnel Management.; Management & management techniques.; elektronické knihy; electronic books